Fatigue modelling for gas nitriding (Fracture and Structural Integrity, 2016)
The present study aims to develop an algorithm able to predict the fatigue lifetime of nitrided steels. Linear multi-axial fatigue criteria are used to take into account the gradients of mechanical properties provided by the nitriding process. Simulations on rotating bending fatigue specimens are made in order to test the nitrided surfaces. The fatigue model is applied to the cyclic loading of a gear from a simulation using the finite element software Ansys. Results show the positive contributions of nitriding on the fatigue strength.
Keywords: Nitriding; Fatigue; Lifetime